2016
DOI: 10.1186/s12885-016-2914-9
|View full text |Cite
|
Sign up to set email alerts
|

Activins and their related proteins in colon carcinogenesis: insights from early and advanced azoxymethane rat models of colon cancer

Abstract: BackgroundActivin-A may exert pro- or anti-tumorigenic activities depending on cellular context. However, little is known about its role, or the other mature activin proteins, in colorectal carcinoma (CRC). This study measured the expression of activin βA- & βB-subunits, activin type IIA & IIB receptors, smads 2/3/4/6/7 and follistatin in CRC induced by azoxymethane (AOM) in rats. The results were compared with controls and disseminated according to the characteristics of histopathological lesions.MethodsEight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…Moreover, the p21, p27, Casp-8 and Casp-3 proteins increased with concomitant declines in CCND1, CCND3, BCL2 and survivin in both cell lines with Act-AB. This study agrees with many prior reports and, altogether, suggest that Act-AB could be a Smad4-independent tumour suppressor protein in CRC [7,[37][38][39]. Our data further advocate that the dysregulation of activins could promote the initiation of CRC independent of anatomical site, whereas loss of Act-AB might contribute to the aggressiveness of right-sided neoplasms during the late cancer stages.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the p21, p27, Casp-8 and Casp-3 proteins increased with concomitant declines in CCND1, CCND3, BCL2 and survivin in both cell lines with Act-AB. This study agrees with many prior reports and, altogether, suggest that Act-AB could be a Smad4-independent tumour suppressor protein in CRC [7,[37][38][39]. Our data further advocate that the dysregulation of activins could promote the initiation of CRC independent of anatomical site, whereas loss of Act-AB might contribute to the aggressiveness of right-sided neoplasms during the late cancer stages.…”
Section: Discussionsupporting
confidence: 93%
“…Concurrently, restoring activin type IIA receptor in mutated malignant enterocytes provoked smad4dependent cell cycle arrest and apoptosis, implying that cancerous cells could bypass the Act-A anti-cancer actions by developing mutations in the Acvr2a or Smad4 genes [14,15]. Moreover, CRC induction in murine elevated Act-A and inhibited Smad4 proteins, whilst hesperidin treatment decreased the tumour numbers and increased the levels of Act-A and Smad4 in malignant tissues [7,33]. By contrast, others have suggested that Act-A is oncogenic since the βAsubunit mRNA and protein alongside Act-A levels increased with CRC progression and linked directly with poor prognosis [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…However, more studies involving the different activin type I and II receptors together with Smads 1/5/8, are still needed to validate our hypothesis. FS tightly controls the biological actions of activins by irreversible binding [7,47]. Additionally, FS is pathologically altered in a variety of solid tumours and is thought to counteract the effects of Act-A [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations